The Impact of Energy Crop Production on Land Use in Hungary - Lászlók, Annet (Zeszyty Naukowe SGGW w Warszawie - Problemy Rolnictwa Światowego, 2012)
Use of land, as a limited resource is gaining importance due to the rapid growth of Earth’s population, the subsequently increasing demand for energy and the presumed impact of climate changes. Despite of the land being a specific resource, as lots of experiences confirm, in most of the countries, as in Hungary, it is not managed optimally. It is a question whether the optimum balance can be reached between different land utilization and production methods and not harming food supply safety but improving the competitiveness of agriculture, decreasing the energy dependence and avoiding an excessive use of soils. The paper analyses the impact of energy crop production on land utilization in Hungary. The current production and technology on the available land cannot satisfy the total energy need by bioenergy. But if land is used which is not cultivated at present due to economic reasons and the possibilities of by-products available in great quantities are exploited, the Hungary’s EU commitment can be fulfilled by 2020. and the country will not risk food production losses or modify the land use considerably.